Phylogenomic analyses support a new subgenus, Rojovitis, of the grape genus Vitis from Mexico - Wen, Jun; Quintanar Castillo, Angélica; Pace, Marcelo R.; Talavera, Alicia; Sparreo, Luke; Johnson, Gabriel; Krupnick, Gary A.; Nie, Ze-Long (Frontiers in Plant Science, 2025)
Despite the tremendous economic significance of grapes, the systematics of the grape genus remains understudied. Based on recent fieldwork, phylogenomic analyses using both nuclear and plastid genomes, as well as morphological comparisons, we report a new grape subgenus, Rojovitis, endemic to Mexico. The new subgenus constitutes a clade that diverged early in the evolutionary history of Vitis, yet there is cytonuclear discordance in its position, suggesting hybridization is a likely mechanism in its origin. Subgenus Rojovitis contains two species, Vitis martineziana J. Wen from Chiapas and V. rubriflora J. Wen from Jalisco, both new to science. In comparison to the two other subgenera of the grape genus (subgenus Vitis and subgenus Muscadinia), Rojovitis is characterized by its red flowers and stems with prominent lenticels. The discovery of the third subgenus in Vitis, nearly a century after the recognition of the second subgenus, Muscadinia, in 1927, represents a major milestone in the systematic research of grapes and their wild relatives. We also use fieldwork and herbarium data to provide distribution maps and conservation assessments of V. martineziana and V. rubriflora based on IUCN criteria. Both species are assessed to be critically endangered. These findings highlight Mexico as an important region for wild grape resources. The study also demonstrates that biodiversity discovery is far from complete today and that field exploration remains critical for biodiversity science and conservation. These newly discovered resources may benefit humanity, yet these species urgently need to be protected and properly managed due to extensive habitat loss and alteration.